2020
DOI: 10.1016/j.ajo.2019.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Can Baseline Computed Tomography Scans Be Used to Identify Patients at High Risk of Vision Loss due to Terson Syndrome?

Abstract: To determine if routinely performed computed tomographic (CT) scanning in patients with aneurysmal subarachnoid hemorrhages (aSAHs) is sufficient to identify patients at high risk of vision loss due to Terson syndrome (TS). METHODS: Consecutive patients with a diagnosis of aSAH admitted to the neurologic intensive care unit of a regional referral hospital over a 3-year period were prospectively evaluated. Head CT scans performed in the emergency department were assessed for the presence of a ''crescent sign'' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 45 publications
0
16
0
1
Order By: Relevance
“…Stewart et al 13 Prospective study with 117 patients with aneurysmal SAH The patient presented visual acuity of 30 cm in the right eye and 0.6 in the left eye when counting the fingers. CT and MRI did not show changes in the visual pathways.…”
Section: Citation Methods Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stewart et al 13 Prospective study with 117 patients with aneurysmal SAH The patient presented visual acuity of 30 cm in the right eye and 0.6 in the left eye when counting the fingers. CT and MRI did not show changes in the visual pathways.…”
Section: Citation Methods Resultsmentioning
confidence: 99%
“…22 In contrast, Stewart et al, in their prospective study, found an increased signal sensitivity (presence of significant sub-internal limiting hemorrhage of the membrane) on CT for the diagnosis of TS in 85.7% high-risk patients and 99.1% specificity. 13 Kang et al, reports that other conditions, such as leukemia, can lead to retinal hemorrhage, suggesting a simultaneous pathogenesis with Terson's syndrome. 5…”
Section: Joswig Et Al Retrospectively Evaluated 36 Patients With Ts Amentioning
confidence: 99%
“…Head computerized tomography (CT) scans requested during the monitorization of the neurological condition were reviewed to determine if a crescent sign in the posterior pole of the eye was present, which would constitute evidence of sub-ILM haemorrhage. 8 …”
Section: Methodsmentioning
confidence: 99%
“…Alternative theories suggest that subarachnoid blood may pass into the cerebrospinal fluid surrounding the optic nerve or cause veins within the optic nerve sheath to rupture and then progress through the retinal layers, internal limiting membrane (ILM), and posterior hyaloid membrane, 8 or that subarachnoid blood in skull base cisterns near the optic nerve is refluxed into the globe through glymphatic channels, leading to intraocular hemorrhage. 3 …”
Section: Introductionmentioning
confidence: 99%
“…In einer Studie der Mayo Clinic Florida, welche sich auf retinale Blutungen mit einem Durchmesser von 2 mm oder mehr fokussiert, wurden eine Sensitivität von 85,7 % und eine Spezifität von 99,1 % erreicht. Die Autoren sehen hierin eine effiziente Selektionsmöglichkeit und Alternative zur initialen ophthalmologischen Untersuchung am Patientenbett als klinische Routine [6].…”
Section: Diskussionunclassified